The determinants of foreign portfolio investment inflows in Malaysia / Muhammad Amirul Anuar - Anuar, Muhammad Amirul (2022)
Foreign portfolio investment (FPI) comprises of securities and other financial assets held by foreign investors that invest in Malaysia. A variety of determinants include in this research. They are gross domestic product (GDP) growth rate, tax cuts, exchange rate, external debt, and interest rate play an important role in attracting steady and smooth foreign investment in developing countries. This study examined the determinants of FPI inflows in Malaysia. This study is using the time series data. The study uses quarterly data covering the periods 2001 to 2020 and the ordinary least square regression model is applying to estimate the relationship of dependent and independent variables. Only secondary data are utilised in this study, which are already published and may be obtained from earlier journals or publications, and regression analysis is performed to analyse the data. In order to get the findings, this study employed E-Views to run all of the acquired data. The finding in this research shows that all the independent variable significant toward the F PI inflows in Malaysia.